Bruce Wayne : not super - Gibbs, Stuart, 1969-; Pekmezci, Berat, 1986-; Esposito, Taylor (Burbank, CA : DC Comics, 2023)
Bruce Wayne, the only kid in school without super powers, gets called to the principal because his career choice of vigilantism is deemed too ambitious, and he becomes even more determined to prove he belongs.
"Batman created by Bob Kane with Bill Finger - Superman created by Jerry Siegel and Joe Shuster. By special arrangement with the Jerry Siegel family"
new kids book 2023 summer.
Ages 8-12
Grades 4-6
Keywords: Identity -- Fiction; Belonging -- Fiction; Superheroes -- Fiction; Gotham City (Imaginary place) -- Fiction; Graphic novels